Extraction, Revolution, Plurinationalism: Rethinking Extractivism from Bolivia. (March 2019) - Marston, Andrea; Kennemore, Amy
With the ratification of its new constitution in 2009, Bolivia was transformed into a "plurinational state" associated with ecologically oriented values, yet resource extraction has expanded ever since. Fieldwork conducted in communities in highland Bolivia shows how resource extraction sustains and is sustained by "revolutionary narratives" in which the state—led by President Evo Morales—is configured as the protagonist of the plurinational era. Examination of the challenges presented by Bolivia's indigenous communities and mining cooperatives to this revolutionary narrative during the 2014 adoption of new mining legislation suggests that shifting critical focus away from revolutionary change toward what David Scott calls the "politics of the present" might be a more fruitful way to think about the relationship between resource extraction and Bolivia's plurinationalism. Al ratificar su nueva constitución en 2009, Bolivia se transformó en un "estado plurinacional" asociado con valores ecológicos; sin embargo, la extracción de recursos se ha expandido desde entonces. Investigaciones llevado a cabo en comunidades de las tierras altas de Bolivia muestran cómo la extracción de recursos sostiene y se sustenta en las "narrativas revolucionarias" en las que el estado, encabezado por el presidente Evo Morales, se configura como el protagonista de la era plurinacional. Examinar como las comunidades indígenas y las cooperativas mineras de Bolivia cuestionaron esta narrativa revolucionaria durante la adopción de la nueva legislación minera en 2014 sugiere que virar el enfoque crítico desde el cambio revolucionario hacia lo que David Scott llama la "política del presente" podría ser una forma más fructífera pensar en la relación entre la extracción de recursos y el plurinacionalismo boliviano.